Pirolisis Kulit Kayu Pinus (Pinus Merkussi) Menjadi Bio-Oil Menggunakan Katalis NiMo/NZA - Sari, Ranum Anggun; Bahri, Syaiful; Khairat, Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Availability of fosil fuel cell that is increasingly limited has already global issue in the world, especially Indonesia. This has an impact onrising extraction costs and selling prices to the public. In addition, the emissions produced by during fossil fuels had a devastating impact on the environment. One of the alternative energy to reduce fossil fuel is bio-oil produced from biomass through pyrolysis technology. Pine bark isa potensial biomass to be used as bio-oil material. Until now, this pine bark only regarded as wastes that pollute the environment. Thought pine bark can be used as a source of fuel, because the pine bark has a potential source of energy. The purpose of this study is to know the effect of the ratio impregnated metal of Ni and Mo on NZA catalyst and the ratio amount of catalyst on the yield of bio-oil produced, knowing the value of density, viscosity, acidity and a flash point of bio-oil as well as determine the chemical components in bio-oil by GC-MS method. Pyrolysis bio-oil begins to process the biomass size reduction (-60+80 mesh) and natural zeolite (-100+200 mesh). Metal Ni and Mo was impregnated into the zeolit to form a bimetallic catalyst NiMo/NZA. Then the catalyst was activated by calcination stage, oxidation and reduction pyrolysis using pine bark as much as 50 grams along with 500 ml silinap with variations developing of metal Ni and Mo to NZA without metal (0%), 1%, 2% and 3% b/b and weight variation of NiMo catalyst/NZA 3%, 6% and 9% of the biomass with a stirring speed of 300 rpm and temperature of 320 oC for 120 min. The highest yield of bio-oil obtained by the use of 3% catalyst NiMo/NZA with 6% of the amount of catalyst which is equal to 77,23%. From physic analysis conducted on bio-oil werw obtained: the density is 0,79 g/ml, the viscosity is 9,87 cSt, the acidity is 5,13 mg NaOH/g sample and the flash point 52 oC. Five (5) the dominant compound results of chemical analysis by GC-MS of the bio-oil from pine bark using 3% catalyst of NiMo/NZA with 6% the amount of catalyst: 2-Pentene (21,8%), Pentane (13,71%), 2-Hexene (8,98%), 1-Propene (7,08%) and 1-Pentene (5,03%).Keywords: bio-oil, catalyst NiMo/NZA and pyrolysis.